Pemberdayaan Kelompok Pengolah dan Pemasar (POKLASAR) Ikan Bandeng untuk meningkatkan pendapatan di Kecamatan Babelan Kabupaten Bekasi Provinsi Jawa Barat - Iis Jubaedah; Asep Akhmad Sugiono; Nadia Ainum Luthfiadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Babelan District, Bekasi Regency has an area of 63.60 km2, and has 87 fishery households (RTP) consisting of 46 RTP (fishermen), 35 RTP (cultivators), and 6 RTP (fishery product processors), which are quite potential to fishery business development. The processors have not taken advantage of the catch or the unsold fish culture because it is not in accordance with market demand so that sometimes fish are abundant and fish prices go down. In addition, the knowledge and skills of the processors are still lacking in diversification of processed fish made from raw fish and marketing which is only carried out around the area. district offline. The purpose of counseling is to increase knowledge, attitudes and skills in processing various types of processed fish made from raw fish and increase income. The extension method used is demonstration, discussion and practice. Data analysis was done descriptively. The target of the extension is the processing and marketer group in Babelan District. Extension materials regarding thorn-pulling milkfish, thorn-pulling milkfish Pepes, fishbone crackers and offline and online-based marketing. The results of the extension evaluation showed that the knowledge, attitudes and skills of the processing group and marketers had increased. Some POKLASAR are skilled in processing various kinds of processed fish raw materials and doing marketing online and offline.